Analisis Aspek Struktural Program Bimbingan dan Konseling: Studi Kasus di Sekolah Menengah Atas Kota Bandung - Irfan Fauzi; Uman Suherman; Yusi Riksa Yustiana (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This study aims to analyze in detail the structural aspects contained in the guidance and counseling program in Bandung high schools. This research uses a qualitative approach, the type of method is a case study. This study involved 2 guidance and counseling teachers to be interviewed with the aim of seeing the conception of meaning from the structural aspects of the guidance and counseling program in the school. Interviews and documentation studies are used as data collection techniques. The data analysis uses qualitative methods such as data reduction, data presentation, and conclusions. The results of this study show that the guidance and counseling program in the senior high schools studied has led to a comprehensive guidance and counseling program, where the aspects contain the principle of developing potential, facilitating the achievement of developmental tasks, creating a supportive environment, including developing skills in decision making. This research contributes to education in an effort to plan and create a comprehensive guidance and counseling program, so that it can have a positive and significant impact on the potential development of students.